Biological oriented preparation technique (BOPT) for tooth preparation: A systematic review and meta-analysis - Afaf Al-Haddad; Noor Addeen Abo Arsheed; Ang Yee; Shivani Kohli (Elsevier, 2024)
Purpose: This systematic review is aimed to evaluate in fixed prosthodontics treated teeth, the effect of the BOPT on periodontal health compared to the horizontal preparation technique using a chamfer finishing line or to the baseline. Methods: The electronic databases Cochrane Central Library, PubMed, Scopus, and ScienceDirect were searched based on specific MeSH keywords. The Randomized controlled clinical trials (RCTs) and prospective clinical trials on BOPT printed in English up to July 2022 were selected. Screening, selection, and data extraction were done. The studies were assessed for risk of bias, and descriptive and meta-analyses were performed. Results: Eight studies were included in the systematic review and only three RCTs were involved in the meta-analysis. Two RCTs were assessed as low risk while one has some concerns. were grouped as good, fair, and poor based on NOS. Three of the prospective studies were considered to be of good quality and one study was fair. The meta-analysis revealed no statistically significant difference in the effect of BOPT and chamfer preparation on periodontal health status and success rate (P > 0.05). Conclusions: Considering the limitation of this review, the BOPT is comparable to chamfer preparation and it resulted in an acceptable effect to maintain periodontal health with a high success rate. However, more evidence is required to support these findings.